2014
DOI: 10.21236/ada611716
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Background Pressure on the Plasma Oscillation Characteristics of the HiVHAc Hall Thruster

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…A detailed analysis of the far-field probe data was performed by Huang. et al 16 , and the plume study revealed that increasing the facility background pressure resulted in changes to how the HiVHAc EDU thruster was operating. The study found that increased background pressure resulted in the average charge state rising rapidly and then leveling off with rising background pressure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed analysis of the far-field probe data was performed by Huang. et al 16 , and the plume study revealed that increasing the facility background pressure resulted in changes to how the HiVHAc EDU thruster was operating. The study found that increased background pressure resulted in the average charge state rising rapidly and then leveling off with rising background pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Huang et al 16 used Faraday, E×B, and retarding potential analyzer probes to gain insights to help us understand how increasing the facility background pressure affects thruster operation and performance. The various probe data is used to estimate thruster discharge efficiency by use of a phenomenological efficiency model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 These diagnostics include thrust stand, Faraday probe, ExB probe, and retarding potential analyzer. 17 The test results indicated a rise in thrust and discharge current with background pressure. The I-V characteristics also varied with background pressure.…”
Section: High Voltage Hall Acceleratormentioning
confidence: 97%